Settlement analysis of two-layer cross-anisotropic media beneath a uniform strip of load by finite element - Acupan, Antonio C. (1984)
An elasticity solution is presented for two layer cross-anisotropic (transversely isotropic) media having a finite depth and loaded using the infinite element method. The general solution was obtained for perfectly flexible and perfectly rigid structure. Numerical results were presented for cases of varying depth of the stiff upper layer and different degrees of anisotropy. The solution can also be reduced to the case of a single layer isotropic medium underlain by a rigid stratum and compared with the available results.